Poly(exTTF): A Novel Redox‐Active Polymer as Active Material for Li‐Organic Batteries. Issue 15 (23rd May 2014) - Häupler, Bernhard; Burges, René; Friebe, Christian; Janoschka, Tobias; Schmidt, Daniel; Wild, Andreas; Schubert, Ulrich S.
<x xml:space="preserve">Abstract</x> The first polymer bearing exTTF units intended for the use in electrical charge storage is presented. The polymer undergoes a redox reaction involving two electrons at −0.20 V vs Fc/Fc+ and is applied as active cathode material in a Li‐organic battery. The received coin cells feature a theoretical capacity of 132 mAh g−1, a cell potential of 3.5 V, and a lifetime exceeding more than 250 cycles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>